Minimum Number of Soil Moisture Sensors for Monitoring and Irrigation Purposes - Lincoln Zotarelli; Michael D. Dukes; Marcelo Paranhos (EDIS)
Managing soil moisture properly through irrigation is key to increasing crop yield and conserving water. By understanding soil moisture variability, growers can better manage their irrigation systems to apply the right amount of water at the right time. This 4-page fact sheet proposes guidelines for soil moisture sampling that account for spatial variability, which helps to determine the minimum number of soil moisture sensors required to survey and monitor a specific area for irrigation. Written by Lincoln Zotarelli, Michael D. Dukes, and Marcelo Paranhos, and published by the UF Department of Horticultural Sciences, July 2013.